2018
DOI: 10.1155/2018/9412782
|View full text |Cite
|
Sign up to set email alerts
|

Load Balancing Opportunistic Routing for Cognitive Radio Ad Hoc Networks

Abstract: Recent research activities have shown that opportunistic routing can achieve considerable performance gains in Cognitive Radio Ad hoc Networks (CRAHNs). Most of these studies focused on designing appropriate metrics to select and prioritize the forwarding candidates. However, in multiple-flow networks, a small number of nodes may always be with the higher priority order for different flows. Thus, some nodes may easily become overloaded with too much traffic and be severely congested. To overcome this problem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…An opportunistic routing protocol was proposed to increase the reliability in CRAHN [7]. In this links are scored using reliability metric and this score is used for next hop selection in the routing protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An opportunistic routing protocol was proposed to increase the reliability in CRAHN [7]. In this links are scored using reliability metric and this score is used for next hop selection in the routing protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But it did not deliberate the suspension, dynamic ingestion and triumph level of data transfer. In LBOR [9], the metric of effective forwarding rate (EFR) is introduced, which indicates the success rate of data transmission of each candidate link in the opportunistic module. But it did not consider the delay, energy consumption, interference, traffic load parameters.…”
Section: Problem Identificationmentioning
confidence: 99%
“…They offered a modest investigative exemplary of the suggested ECR in the perspective of network-wide dynamism and associate it with that of the ad hoc on-demand distance vector (AODV) routing procedure. Wenxuan Duan et al [9] have suggested a load balancing opportunistic routing (LBOR) system to exploit the entire output of the entire system. They initially expressed the issue of exploiting the entire output of the system as a rectilinear encoding issue.…”
Section: Related Workmentioning
confidence: 99%
“…A statistical test was conducted to validate the classifier. Load Balancing Opportunistic Routing (18) and Bee Inspired Agent Based Routing (19) proposed to enhance the routing process in CRAHN by without considering the security issues.…”
Section: Introductionmentioning
confidence: 99%